2011
DOI: 10.1111/j.1365-313x.2011.04600.x
|View full text |Cite
|
Sign up to set email alerts
|

Assigning DYW‐type PPR proteins to RNA editing sites in the funariid mosses Physcomitrella patens and Funaria hygrometrica

Abstract: SUMMARYThe plant-specific pentatricopeptide repeat (PPR) proteins with variable PPR repeat lengths (PLS-type) and protein extensions up to the carboxyterminal DYW domain have received attention as specific recognition factors for the C-to-U type of RNA editing events in plant organelles. Here, we report a DYW-protein knockout in the model plant Physcomitrella patens specifically affecting mitochondrial RNA editing positions cox1eU755SL and rps14eU137SL. Assignment of DYW proteins and RNA editing sites might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 56 publications
2
61
0
1
Order By: Relevance
“…For the enzymatic reaction of converting a cytidine to a uridine, a deaminating activity is required. Because a separate enzyme has not been identified so far, it was proposed that possibly one of the additional C-terminal domains directly contributes the enzymatic activity, in cis when present and in trans through heterodimer formation (16,17). We now find that an entirely unexpected class of proteins constitutes an additional, essential component of the plant organellar editosome and is required for processing of almost all editing sites in plastids and of at least many sites in mitochondria.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…For the enzymatic reaction of converting a cytidine to a uridine, a deaminating activity is required. Because a separate enzyme has not been identified so far, it was proposed that possibly one of the additional C-terminal domains directly contributes the enzymatic activity, in cis when present and in trans through heterodimer formation (16,17). We now find that an entirely unexpected class of proteins constitutes an additional, essential component of the plant organellar editosome and is required for processing of almost all editing sites in plastids and of at least many sites in mitochondria.…”
mentioning
confidence: 72%
“…Genes for MORF proteins are only detected in flowering plants (SI Appendix, Fig. S3), and not in the moss Physcomitrella patens (17,28). In this plant, only PPR proteins with C-terminal extended DYW domains are involved in the few editing events.…”
Section: Discussionmentioning
confidence: 99%
“…The very few RNA editing sites in the moss-only eleven in mitochondria and only two in chloroplasts-and its amenability to targeted nuclear gene knockouts make Physcomitrella an attractive complementary model system. Knockout analyses in Physcomitrella patens have so far clearly assigned six of its ten DYW-type PPR proteins to nine of its eleven mitochondrial editing sites (Ohtani et al 2010;Tasaki et al 2010;Rüdinger et al 2011;Uchida et al 2011). Three of these DYW proteins address two editing sites simultaneously, possibly due to the sequence similarities around those editing sites.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 200-500 RNA editing sites are present in flowering plant mitochondria (Giegé and Brennicke 1999;Notsu et al 2002;Handa 2003;Mower and Palmer 2006;Sloan et al 2010), but RNA editing frequencies vary even more widely in other plant clades. Less than a dozen sites are affected in the mitochondrial transcriptomes of funariid mosses (Rüdinger et al , 2011, whereas more than 2000 RNA editing events have been found in the spikemoss Selaginella moellendorffii, a lycophyte representing an ancient vascular plant lineage (Hecht et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3). The assigned five medium, long, and short elements in MEF8 and MEF8S furthermore deviate from the characteristic amino acid signature with several of the usually conserved residues substituted by unconventional moieties (17,45,49,50). The E domain shows a deletion of 11 amino acids in MEF8 and of 13 residues in MEF8S in comparison with the E domain consensus arrangement (Fig.…”
Section: Rna-editing Proteins With a Degenerated Ppr Proteinmentioning
confidence: 99%